Transvaginal Small Bowel Evisceration following Abdominoperineal Resection - Enver Kunduz; Huseyin Bektasoglu; Samet Yigman; Huseyin Akbulut (Case Reports in Surgery)
Abdominoperineal resection (APR) is one of the surgical techniques performed for the distal rectal cancer. The perineal herniation is one of the complications of APR surgery. In this report, we aim to demonstrate a rare case of small bowel evisceration and strangulation secondary to the transvaginal herniation evolved in the late stage after perineal hernia repair following laparoscopic APR.